Systematic Literature Review: The Integration of Ethnoscience through Local Wisdom in Science Education and Its Impact on Students' Competencies - Syarifa Rahmi Anori; Fianti Fianti; Sri Sukaesih; Shelly Efwinda (Jurnal Pendidikan Sains Indonesia, 2026)
Science learning is often considered theoretical and insufficiently connected to students’ real-life experiences, resulting in low levels of scientific literacy. The integration of ethnoscience through local wisdom offers a strategic approach to bridging school science and indigenous knowledge. This study aimed to analyze the integration of ethnoscience in science education and its impact on students’ competencies. A systematic literature review (SLR) following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines was conducted using articles published between 2020 and 2025 and indexed in scopus, DOAJ, ERIC, and google scholar. A total of 30 articles that met the inclusion criteria were analyzed thematically. The findings revealed that: (1) physics was the most frequently integrated science domain (40.0%), followed by biology (30.0%) and chemistry (23.3%); (2) traditional foods and local products were the most commonly used forms of local wisdom (30.0%); (3) ethnoscience integration had the greatest impact on cognitive competencies (63.3%), particularly scientific literacy and conceptual understanding, followed by affective competencies (33.3%), including environmental awareness and character development; and (4) traditional food contexts were predominantly associated with cognitive competency development, whereas environmental conservation practices were more strongly linked to affective competency development. Overall, ethnoscience serves as an effective bridge between scientific knowledge and local culture, supporting the holistic development of students’ competencies. This review proposes a conceptual model of ethnoscience integration that can guide educators and curriculum developers in designing innovative, meaningful, and culturally responsive science learning